2015
DOI: 10.1002/smll.201501167
|View full text |Cite
|
Sign up to set email alerts
|

Peptide‐like Polymers Exerting Effective Glioma‐Targeted siRNA Delivery and Release for Therapeutic Application

Abstract: Lipopolymer 49, a solid-phase synthesized T-shaped peptide-like oligoamide containing two central oleic acids, 20 aminoethane, and two terminal cysteine units, is identified as very potent and biocompatible small interfering RNA (siRNA) carrier for gene silencing in glioma cells. This carrier is combined with a novel targeting polymer 727, containing a precise sequence of Angiopep 2 targeting peptide, linked with 28 monomer units of ethylene glycol, 40 aminoethane, and two terminal cysteines in siRNA complex f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 36 publications
0
29
0
Order By: Relevance
“…Combined administration of PPAR γ ligand and its antagonist targeted 14-3-3 gamma and BIS, inhibiting stem cell-like properties in GSC-like spheres expressing SOX2. Our findings provide additional evidence that BIS may be a potential target in glioblastoma [38]. …”
Section: Discussionmentioning
confidence: 53%
“…Combined administration of PPAR γ ligand and its antagonist targeted 14-3-3 gamma and BIS, inhibiting stem cell-like properties in GSC-like spheres expressing SOX2. Our findings provide additional evidence that BIS may be a potential target in glioblastoma [38]. …”
Section: Discussionmentioning
confidence: 53%
“…Thus, our results suggested that BIS depletion is an effective strategy for directly targeting STAT3 to accelerate its degradation. Recently, two groups independently reported the successful delivery of BIS siRNA to glioblastoma or squamous cell carcinoma models using peptide-like polymers or gold-nanorod-siRNA nanoplexes [50, 51]. These findings indicated that the increased efficacy of BIS-siRNA delivery techniques might advance the therapeutic application of BIS targeted to suppress tumor progression by inhibiting the anti-apoptotic effect of BIS, as well as STAT3-mediated CSC progression.…”
Section: Discussionmentioning
confidence: 99%
“…The BBB is especially restrictive in normal healthy brain, but also a barrier in diseased brain such as glioma. In order to generate stable polyplexes in a size range suitable for glioma‐targeted siRNA delivery across the BBB, a solid‐phase synthesized lipo‐oligomer (49) containing two central oleic acids, 4 Stp units and two terminal cysteines has been combined with a lipoprotein receptor ‐ related protein LRP‐targeting oligomer containing a precise sequence of Angiopep‐2 peptide linked with PEG, 8 Stp units and two terminal cysteines (727) (Figure a). siRNA‐polyplexes around 100 nm in size with low polydispersity and nearly neutral zeta potential could be generated.…”
Section: Polyplexes In Vivomentioning
confidence: 99%
“…High amounts of fluorescently labeled siRNA could be detected in the brain when targeted polyplexes where applied (Figure d). BAG3 siRNA was chosen as therapeutic cargo . BAG3 is a member of the BAG family of HSC/HSP70 co‐chaperones, which plays a critical role in tumor cell survival .…”
Section: Polyplexes In Vivomentioning
confidence: 99%